Challenges in Management of VTE in Children With Cancer: Risk Factors and Treatment Options - Samji, Nasrin; Bhatt, Mihir D.; Kulkarni, Ketan (Frontiers in Pediatrics, 2022)
Venous thromboembolism (VTE) occurs in 2.1- to up to 50% of children with cancer and contributes to long term morbidity as well as early mortality in this population. Pediatric patients with malignancy are predisposed to VTE due to the prothrombotic nature of cancer and its associated coagulopathies as well as chemotherapeutic agents, use of central venous catheters, surgery, radiotherapy, and concomitant thrombophilia. Management of thrombosis in this population is challenging due to concomitant thrombocytopenia, associated bleeding risks, concurrent co-morbidities, and toxicities of therapy. The aim of this paper is to highlight clinically relevant issues and management dilemmas using clinical vignettes. We review the clinical significance of asymptomatic and symptomatic thrombosis, examine the various options for asparaginase-associated thrombosis, address the role and controversies of direct oral anticoagulants, and describe our approach to managing anticoagulation therapy in the context of chemotherapy-induced thrombocytopenia.